Performance variables and technical penalties of the split leap - Rodriguez Galán, M.; Gómez-Landero Rodriguez, L. A. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2018)
The aim of this study was to analyze the relationship betweenthe following aspects: the technical penalties obtained in the execution of an isolated gymnastics element, the competitive level of the gymnasts, their anthropometric characteristics, and the most important temporal and angular variables analyzed in this skill. Twenty nine gymnasts (aged 17.1 ± 3.1 years) from different competition levels were selected. Three coaches evaluated the execution through an adaptation of the Code of Points. Significant direct and indirect associations were observed (p < 0.05): low adiposity index (rho = 0.643), take-off total time (rho = 0.619), flight total time (rho = -0.596), maximum range of motion of the hips (rho = -0.902), and maximum extension of ankles (rho = -0.738). The assessment of penalties as well as the use of competitive level and Split Leap as specific tests, have demonstrated to be useful tools for evaluating performance.